STUDENTS RESPONSE TOWARD THE USE OF SCANNING TECHNIQUE IN READING RECOUNT TEXT - Yudi Lesmana; Setya Resmini (IKIP Siliwangi, 2020)
The intention of this research is to know the students’ responses toward the use of a scanning technique in reading recount text. Scanning technique is either of alternative ways to reading especially in reading recount text because it could help students to easy to find the answer of the test with used multiple-choice form, students will respond to the question quickly. This research used descriptive qualitative method and the participant of this research was in the eighth grade of a Junior High School in Bandung. This research has been implemented by giving questionnaires consisted of positive and negative statements. The results show that almost all of the students (71.80%) agree that the use of scanning techniques in reading on recount text becomes easy and they can understand the text well and fast and answer in a simple way.